Nucleus‐Targeted Organoiridium–Albumin Conjugate for Photodynamic Cancer Therapy. Issue 8 (21st January 2019) - Zhang, Pingyu; Huang, Huaiyi; Banerjee, Samya; Clarkson, Guy J.; Ge, Chen; Imberti, Cinzia; Sadler, Peter J.
Abstract: An organoiridium–albumin bioconjugate (Ir1‐HSA ) was synthesized by reaction of a pendant maleimide ligand with human serum albumin. The phosphorescence of Ir1‐HSA was enhanced significantly compared to parent complex Ir1 . The long phosphorescence lifetime and high 1 O2 quantum yield of Ir1‐HSA are highly favorable properties for photodynamic therapy. Ir1‐HSA mainly accumulated in the nucleus of living cancer cells and showed remarkable photocytotoxicity against a range of cancer cell lines and tumor spheroids (light IC50 ; 0.8–5 μm, photo‐cytotoxicity index PI=40–60), while remaining non‐toxic to normal cells and normal cell spheroids, even after photo‐irradiation. This nucleus‐targeting organoiridium‐albumin is a strong candidate photosensitizer for anticancer photodynamic therapy. Abstract : On target : A nucleus‐targeted organo‐iridium‐HSA conjugate for photodynamic therapy has been developed. Phosphorescence of a weakly emissive maleimide‐functionalized Ir complex is greatly enhanced when conjugated to human serum albumin. The iridium‐HSA conjugate targets the nucleus and generates 1 O2 for photodynamic therapy upon irradiation with visible light.